2016
DOI: 10.18632/oncotarget.9350
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA DANCR promotes invasion of prostate cancer through epigenetically silencing expression of TIMP2/3

Abstract: LncRNA DANCR suppresses differentiation of epithelial cells, however, its function in prostate cancer development is still unknown. In the present study, we found the expression of DANCR increases in prostate cancer tissues and cells compared to normal prostate tissues and cells, moreover, DANCR promotes invasion and migration of prostate cancer cells in vitro and metastasis of tumor xenografts in nude mice. Mechanistically, we found that TIMP2/3, which are critical metastasis inhibitor of prostate cancer, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
119
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(124 citation statements)
references
References 39 publications
4
119
0
1
Order By: Relevance
“…EZH2, a histone methyltransferase and the catalytic component of polycomb repressive complex 2, is responsible for H3K27me3 trimethylation and repression of target genes (Chang & Hung, ). Similar to the studies of Jia et al, () and Yi et al, () we found that EZH2 could also bind to the promoter of TIMP2 in human ectopic endometrial epithelial cells. In addition, the decreased binding of EZH2 and TIMP2 by TUG1 knockdown further confirmed this conclusion.…”
Section: Discussionsupporting
confidence: 91%
“…EZH2, a histone methyltransferase and the catalytic component of polycomb repressive complex 2, is responsible for H3K27me3 trimethylation and repression of target genes (Chang & Hung, ). Similar to the studies of Jia et al, () and Yi et al, () we found that EZH2 could also bind to the promoter of TIMP2 in human ectopic endometrial epithelial cells. In addition, the decreased binding of EZH2 and TIMP2 by TUG1 knockdown further confirmed this conclusion.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, the potential role of DANCR in cancer has been reported in several studies; however, these studies showed that DANCR plays opposite roles depending on the tumour type. In colorectal cancer, hepatocellular carcinoma and prostate cancer, DANCR functions as an oncogene; on the contrary, another report indicated that DANCR functions as a tumour suppressor in breast cancer via degrading the epigenetic tumour regulator EZH2 [13][14][15][16]. This phenomenon may explain the variable expression and biological patterns of DANCR in different cancer types.…”
Section: Discussionmentioning
confidence: 98%
“…17 The primer sequences were as follows: PSA (F: 5′-GTGTGTGGACCTCCAT-GTTATT-3′, R: 5′-CCACTCACCTTTCCCCTCAAG-3′); FKBP5 (F:…”
Section: Real-time Quantitative Polymerase Chain Reaction Assaymentioning
confidence: 99%